Horse‐keeping practices in Australia: findings from a national online survey of horse owners. Issue 11 (27th October 2017) - Thompson, KR; Clarkson, L; Riley, CB; van den Berg, M
Abstract : Objective: To gain an understanding of general horse‐keeping practices in Australia, including shelter, social contact, exercise, watering and supplementary feeding. Methods: An online survey was conducted with 505 owners in relation to one 'representative' horse in their care. Results: The majority (83%) of horses were managed at pasture. Approximately one‐quarter of those horses were housed alone (26%) or with one companion animal (27%). If horses were confined to a stable or small yard, the most recorded means of exercise was riding (65%) at a daily frequency (60%). Over half of the horse owners provided water in a trough or drinker with an automatic refill system (58%) and most horse owners supplied hay to their horses (82%), most commonly in combination with grazing. Areas of potential concern included one‐quarter of stabled horses being prevented from unmediated social and physical contact with conspecifics and one‐fifth of stabled horses being exercised less than daily. Conclusion: The horse‐keeping profile in this study should be considered in the public communication of guidelines as well as interactions between veterinarians and clients.